Socialization of the Importance of Halal Product Certificate Literacy in Gunung Anyar District, Surabaya City - Kunsah, Bateru; Luluk Latifah; Salim, Lutfi Agus (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2025)
There are many aspects that need to be considered for Micro, Small and Medium Enterprises (MSMEs) in the culinary sector, one of which is taking care of halal certification. The certificate issued by the Halal Product Assurance Agency (BPJPH) is important for Micro, Small and Medium Enterprises (MSMEs) actors. Moreover, the majority of the population in Indonesia embraces Islam and requires halal guarantees for the culinary products consumed. Halal certification has the benefit of increasing consumer confidence, increasing market share, and increasing business competitiveness. By having a halal certificate, Micro, Small and Medium Enterprises (MSMEs) products will be more accepted in the market, especially among Muslim consumers who need halal products to be safer when consumed. The Halal Product Assurance Agency (BPJPH) has reopened the Free Halal Certification (SEHATI) program with a quota of 1 Million Certificates and every Micro, Small and Medium Business actor can register in early January 2025 and the phasing of halal certification obligations will end on October 17, 2026. The participants of this community service are women food and beverage business actors in the city of Gunung Anyar sub-district, Surabaya City. These women who have a food and beverage business do not know how to register halal certification for their Micro, Small and Medium Enterprises. So that these business actors are very enthusiastic to know the process from the beginning of registration until the halal certificate is issued